Wat werkt er en hoe? Het common factors model als basis voor de hulpverlening in het sociaal werk. - Sjef de Vries (Journal of Social Intervention: Theory and Practice, 2017)
What works and how?  The common factors model as a basis for psychosocial support in social workPsychosocial support in social work in the Netherlands is generalistic, eclectic and integral. Research into the active components therein is scarce. One of the reasons is that the medical model, a meta-model that explains what works in therapy, counseling and support, dominates. The core of the medical model is that specific methods and techniques are remedial for specific problems. The conditions for a method to be effective are: a diagnosis of a specific problem, a psychological explanation of that problem, a theory of change, and the application of (evidence-based) specific techniques. The generalistic, eclectic way of working in social work does not fit in with the medical model. The medical model-explanation of what works is strongly present in the development of methods in social work. For example, the 130 methods in the Database Effective Social Interventions (Movisie) are all described along the lines of the medical model. A consequence of the medical model is the ever growing development of specific treatments for new or more specific diagnoses. As a result, social work support threatens to become increasingly specific. A second consequence is that the view on the special qualities and active components of social work support remains underexposed and, therefore, not well understood and studied. That makes improvement difficult. Furthermore, both the perspective and the goal of social work do not correspond with the medical model. An essential aspect of social work is the contextual vision: how problems and solutions are embedded in the social environment and daily life of people. The integral support of people in and with their social context is the concretization thereof. The medical model on the other hand decontextualizes people, it often translates life problems into psychological problems that can be "repaired", isolated from the context of which they are part and from the people that can contribute to its solutions. The purpose of social work – empowerment – also does not correspond well with the medical model. Unlike the medical model, empowerment does not focus on what is missing, insufficient or "sick", but on people’s resources, on what goes well in life or what is "healthy". Empowerment cannot be achieved through interventions according to the medical model. Empowerment as an "end product" through a protocol with prescribed technical procedures and predetermined goals misses the essence of empowerment. Empowerment is a process that gets its content and shape in the dialogue between two equal partners. The process of the clients themselves and not the method is essential. Which facet of empowerment is strengthened, in what (life) area, how that happens and what the end result shall be, it all depends on and is developed through that dialogue. To coach and support that dialogue is the essence of social work. Based on the work of Wampold and Imel (20015), supplemented with (Dutch) social work research, it becomes possible to describe the lack of evidence for the efficacy of specific factors.  Furthermore, the possibilities and scope of the non-specific way of working is brought forward. The common factors are seen as an alternative explanation of what works. The factors that are common to any kind of psychological assistance are a client in his context and a therapist/social worker. Together they create a working relationship (alliance). This relationship awakens placebo effects like hope and is, because of its purpose, structured in a certain way (the method). Scientific evidence connects all those five factors to the outcome. The common factors perspective shows that psychological assistance is an interpersonal, relational phenomenon, not an instrumental one. The common factors perspective changes the view on clients. They are not seen as the recipient of the treatment but as self-helpers who actively maintain the relationship and direct content and goal of the conversations. They have created their own Theory of Change from life experiences. That theory determines what they want and can change and how they can do it in the best way. This active role of clients makes psychosocial assistance a co-operation. A collaboration in which both participants together provide new direction and meaning to problems and solutions is called co-construction. In that, the client and the social worker are equal, each with their own specific expertise. The client is an expert of his own experiences, ideas, expectations, goals, resources. The social worker is an expert in process counseling: in listening, asking questions, and giving information so that he enables the client to make use of what psychosocial support has to offer for achieving his goals. We describe a common factors model that supports and shapes social work support. The model builds on the model of Wampold and Imel (2015) and extends it with the concept of co-construction. In this model, the psychosocial support has four active components: the co-construction of the (personal) working relationship, of hope, of solutions and of the evaluation. The model emphasizes that psychosocial support is an interpersonal process. It points to the importance of the dialogue and the role of the unique characteristics of the participants in it. In addition, it gives room for eclectic work and specific factors. Moreover, it is open to the complexity of problems and the influence of social and cultural aspects the clients brings with him. These (inter)personal and contextual aspects are essential in social work.  SAMENVATTING Wat werkt er en hoe? Het common factors model als basis voor de psychosociale hulpverlening in het sociaal werkPsychosociale hulpverlening in sociaal werk is generalistisch, eclectisch en integraal. Onderzoek naar de werkzame ingrediënten daarin is schaars. Eén van de redenen is dat het medisch model, een metamodel dat verklaart wat werkt in therapie, counseling en hulpverlening, domineert. De kern van het medisch model is dat specifieke methoden en technieken helend zijn voor specifieke problemen. De medisch model-verklaring van wat werkt is sterk aanwezig bij de ontwikkeling van methoden in maatschappelijk werk. Het medisch model is moeilijk te verenigen met het sociaal werk. Niet alleen de niet-specifieke, generalistische manier van werken in het sociaal werk, maar ook de contextuele visie op problemen en oplossingen en het doel van sociaal werk – empowerment – sluiten niet goed aan op het medisch model. Op basis van het werk van Wampold en Imel (2015) en aangevuld met (Nederlands) sociaal werk- onderzoek, wordt in dit artikel het gebrek aan bewijs voor de werkzaamheid van specifieke factoren en de mogelijkheden en reikwijdte van de niet-specifieke generalistische werkwijze beschreven. De “common factors” worden gezien als een alternatieve verklaring van wat er werkt. De factoren hebben een stevige basis in wetenschappelijk onderzoek en correleren met het effect van hulpverlening. In hoofdlijnen wordt een common factors model beschreven als een wetenschappelijke fundering van de psychosociale hulpverlening in het sociaal werk. In dit model heeft die hulpverlening vier werkzame factoren: de co-constructie van de (persoonlijke) werkrelatie, van hoop, van oplossingen en van de evaluatie. Het model benadrukt dat wat werkt in de psychosociale hulp in het sociaal werk een interpersoonlijk proces is, geen instrumenteel. Het ondersteunt het belang van de dialoog en de rol van de unieke kenmerken van de deelnemers daarin. Het staat open voor de complexiteit van de problemen en de invloed van sociale en culturele aspecten die de cliënten meebrengen. Daarnaast biedt het ruimte voor eclectisch werk en de inbreng van specifieke factoren. Deze (inter)persoonlijke en contextuele aspecten en de flexibiliteit in het methodisch handelen zijn essentieel in het sociaal werk om maatwerk te kunnen leveren aan een grote diversiteit van cliënten en hun complexe problemen.